2017
DOI: 10.1590/1980-57642016dn11-010010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sociodemographic variables on executive functions

Abstract: Executive functions (EFs) regulate human behavior and allow individuals to interact and act in the world. EFs are sensitive to sociodemographic variables such as age, which promotes their decline, and to others that can exert a neuroprotective effect.ObjectiveTo assess the predictive role of education, occupation and family income on decline in executive functions among a sample with a wide age range.MethodsA total of 925 participants aged 18-89 years with 1-28 years' education were submitted to assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…In addition, they had higher education and a different racial profile, which may have contributed to differences between studies because education and other sociodemographic variables have been shown to influence performance on executive function tests (Campanholo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they had higher education and a different racial profile, which may have contributed to differences between studies because education and other sociodemographic variables have been shown to influence performance on executive function tests (Campanholo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The MoCA contains more subtests related to executive functions than the MMSE. 10 32 33 The executive function is significantly related to educational level 34 35 36 37 and the neuropsychological characteristic of VaMCI is an executive dysfunction. 38 39 40 Therefore, it can be explained that the MoCA is superior to the MMSE in screening for VaMCI, in which the executive dysfunction is characteristically observed.…”
Section: Discussionmentioning
confidence: 99%
“…Na mesma linha de resultados, os indivíduos com NE alto realizam mais rapidamente o Trail Making Test, um outro teste utilizado na avaliação da flexibilidade cognitiva, do que os participantes com NE baixo (Ganguli et al, 2010;Hamdan & Hamdan, 2009;Oosterman et al, 2021). A partir de uma tarefa de classificação de cartas semelhante ao WCST, Campanholo et al (2017), obtiveram resultados que demonstraram o efeito negativo do NE sobre a flexibilidade cognitiva.…”
Section: Introductionunclassified